Pengaruh Persedian Bahan Baku, Kualits Bahan Baku Dan Proses Produksi Terhadap Kualitas Produk Pada PT.Florindo Makmur - Suryadi, Suryadi; Septiana, Nani; Irfansyah, Irfansyah (Universitas Muhammadiyah Metro, 2023)
This study aims to influence the supply of raw materials, the quality of raw materials, and the production process of the quality of products at PT Florindomakmur. The type of research used is qualitative research. The population in this study were employees who worked at PT Floridamakmur. The sample used was 35 respondents consisting of employees of the raw material processing department, the production process section, and the product quality testing section. The data collection technique used is the dissemination of questionnaires (Questionnaires). Data analysis techniques are qualitative descriptive techniques that aim to analyze a problem that occurs in a study. The analytical tool used in the study was multiple linear regression analysis with the help of a statistical package for social sciences (SPSS) 26. The type of data used is qualitative data. The results of this study explained that the supply of raw materials has a positive and significant effect on product quality, the quality of raw materials has a positive and significant effect on product quality and the production process has a positive and significant effect on product quality at PT Florindomakmur.